PENGARUH ESG, THIN CAPITALIZATION, DAN PERTUMBUHAN PENJUALAN TERHADAP TAX AVOIDANCE: TAX AVOIDANCE - Afifah Pinangsih Isnandi (Yayasan Kayyis Mulia Jaya, 2024)
This study aims to see the effect of ESG, Thin Capitalization, and Sales Growthon Tax Avoidance. This study focuses on food & beverage sub-sector companieslisted on the Indonesia Stock Exchange (IDX) for the 2018-2022 period. Thetype of research used is Quantitative research. The population of this study was62 companies, which were then re-selected using the purposive samplingmethod to produce 8 companies with a sample size of 40. The data used issecondary data in the form of financial reports from each company that hasbeen used as a research sample. The variables used in this study are ESG (X1),thin capitalization (X2), and sales growth (X3), and tax avoidance (Y). The dataanalysis technique used is descriptive statistics and panel data regressionanalysis using eviews-12 software. The results of this study based onsimultaneous tests state that ESG, Thin Capitalization, and Sales Growth havea simultaneous effect on Tax Avoidance. Based on partial tests, it states thatESG has an effect on Tax Avoidance. However, Thin Capitalization and SalesGrowth have no effect on Tax Avoidance. Keywords : ESG; Thin Capitalization; Sales Growth; Tax Avoidance